Inter-Disciplinary Student Work Placements within a Care Home Setting: Improving Student Employability and Developing Social Connections – A Qualitative Evaluation - Mason, Rachael; Hunt, Rachael; Kane, Ros (International Journal of Practice-based Learning in Health and Social Care, 2021)
This article reports on the development, implementation and evaluation of a project to develop students’ employability skills by involving them in work experience within a care home. The aims of this project were (1) to describe how employability skills developed during the work experience (including knowledge and values relevant to the health and social care sector) and (2) to promote social engagement for residents living within the care home. In this descriptive qualitative study, 12 students from various disciplines across social science courses volunteered to participate following an advert to all students. Alongside three key care home staff, these students participated in two information sessions prior to involving residents in individual and group activities commencing in the following week. Qualitative, semi-structured, written evaluations were collected from the students and care home staff at three time points: immediately after the information sessions, immediately following volunteering sessions and at the end of the project, five months after the project commenced. Evaluations were analysed thematically using the principles of Braun and Clarke (2006) with the identified themes demonstrating students had developed skills, knowledge and understanding in the context of caring for older adults through their planning and implementation of activities, engaging and communicating with the residents, and working alongside care home staff. They reported benefiting from working as a team and commented on their perceived benefits to the residents. Students were able to build transferable skills which they felt would benefit them in future employment. Their participation resulted in a greater understanding of caring for older adults which students stated they can apply both in their working and social lives. The project provided an opportunity for peer education and experience of inter-disciplinary teamwork. The perceived benefits to residents included a positive impact on social engagement, communication and well-being.